(untitled) (Research, Society and Development, 2022)
Polymyxins were discovered in the 1940s and were used to treat infections caused by gram-negative bacteria. These molecules act by destroying the cell membrane through the destabilization of phospholipids and lipopolysaccharides (LPS). Due to adverse effects, such as nephrotoxicity and neurotoxicity, this class had seen limited use. However, with the evolution of antimicrobial resistance to commercial drugs, the use of polymyxins has resumed, and over time, strains resistant to this drug have been observed. Currently, resistant bacteria this antimicrobial are found in hospital environments, and non-anthropized environments. This occurrence constitutes a global human and environmental health problem that is of concern to the population, health professionals, and researchers. Thus, this review was conducted with the objective of describing the mechanisms and the occurrence of bacterial resistance to polymyxins, and to demonstrate the relationship between multi-resistant strains of clinical and environmental origins.